Association of Adipocytokines With Carotid Intima Media Thickness and Arterial Stiffness in Obstructive Sleep Apnea Patients - Song, Fan; Zou, Juanjuan; Song, Zhiyuan; Xu, Huajun; Qian, Yinjun; Zhu, Huaming; Liu, Suru; Guan, Jian; Chen, Jie; Yi, Hongliang (Frontiers in Endocrinology, 2020)
Objective: Obstructive sleep apnea (OSA) results in increased carotid intima-media thickness (IMT) and arterial stiffness; however, the association between adipocytokines and IMT/arterial stiffness in OSA patients is unclear. Methods: We enrolled 95 participants from May 2018 to December 2018 in this study. All subjects underwent a carotid artery ultrasound examination and polysomnography. Blood samples were used to determine serum chemerin, adiponectin, SFRP5, and apelin levels. Correlations between two quantitative variables were assessed using the Pearson or Spearman coefficient. Stepwise models of multiple linear regression analysis were performed to assess the independent relationships. Result: IMT in OSA patients was significantly higher than in the nonsnorers. There were significant differences in the arterial stiffness parameters such as distensibility coefficient (DC), compliance coefficient (CC), and pulse wave velocity (PWV). SFRP5 level was lower in OSA patients than in nonsnorers. Adiponectin correlated with CC, DC, and PWV among OSA patients; however, the relationship disappeared after a multivariable adjustment. Age was independently associated with all quantitative IMT and stiffness indices. AHI and minimum oxygen saturation (Mini SaO2) were independently related to arterial stiffness. Conclusion: The quantitative IMT and carotid arterial elasticity were significantly worse among OSA patients. Age was the main independent factor correlated with quantitative IMT and arterial stiffness, and AHI and mini SaO2 were associated factors. There were no relationships between aforementioned adipocytokines and quantitative IMT/carotid arterial stiffness.